The kitchen table talks - immigrant Italian domestic workers in Toronto's post-war years - Weisbart Bellini, Stephanie, 1960- (2001)
Thesis (M.W.S.)--Memorial University of Newfoundland, 2001. Women's Studies Bibliography: leaves 183-198 This thesis examines the labour experiences of post-war immigrant Italian women who were employed as household workers in the greater Toronto area. As a sub-text, it also explores the social construction of fictional immigrant Italian women's lives in Italian- Canadian literature. -- Dorothy Smith's The Everyday World As Problematic (1987), which addresses how ruling relations work through texts, and mat women are generally excluded from ruling relations, provided an analytical context for this thesis. Like Rollins (1985: 8), my approach to this study is based on the notion mat those who have lived an experience know more about it than those who have not. In this case, the experiences of Italian immigrant household workers expressed through oral interviews I conducted, are compared with the images of immigrant Italian women as victims of triple oppression commonly found in Social Science and Popular Literature. -- Extant popular literature on the situation of Italian females in Canada is flowering, but immigrant women have not received proper analysis because their stereotyped image has not been fully debunked. A qualitative analysis shows mat they are portrayed by both female and male writers in a variety of ways, most of which perpetuate stereotypes. First generation Italian immigrant women are characterized in the fiction primarily as wives and mothers, but less often as paid workers. The near invisibility of women workers in the fiction might be related to a difference in intergenerational perceptions. Many literary works of the later generation of Italian-Canadian writers are more feminist in their orientation, and address a broader range of women's issues. -- Italian immigrant household workers were anything but passive victims of job oppression without possibilities of choice, resistance, or independence. By using a variety of strategies for coping within the workplace, women were able to gain a sense of control over their working lives. Italian women worked in the paid and unpaid sectors of the service industry as mothers and wives who performed multiple duties. Many newly-arrived women actively chose paid household employment as a way to market the skills they had developed from child rearing and housekeeping.